2005
DOI: 10.1073/pnas.0508390102
|View full text |Cite
|
Sign up to set email alerts
|

Detection of functional single-nucleotide polymorphisms that affect apoptosis

Abstract: Human EBV-transformed B lymphocyte cell lines (LCLs) were used to measure the apoptotic response of individuals to ␥ radiation. The responses form a normal distribution around a median of 35.5% apoptosis with a range of 12-58%. This heterogeneous response has a genetic basis. LCLs from Caucasian donors and African American donors form distinct distributions of apoptotic response; all of the 11 LCLs comprising the lowest responding group (exhibiting between 12-20% apoptosis) are from Caucasian donors. The assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
92
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 24 publications
3
92
1
3
Order By: Relevance
“…However, lymphocytes from normal Caucasians homozygous for the C-G portion of the haplotype T-C-G have higher levels of AKT1 protein, and lowered reponse to apoptotic stimuli, than those harbouring the T-A haplotype (48). As we found no clear relationship between haplotype and AKT1 transcription in the SBS, further studies are required to elucidate any differential effect in schizophrenic patients (associated with AKT1 or not) versus controls.…”
Section: Discussioncontrasting
confidence: 38%
“…However, lymphocytes from normal Caucasians homozygous for the C-G portion of the haplotype T-C-G have higher levels of AKT1 protein, and lowered reponse to apoptotic stimuli, than those harbouring the T-A haplotype (48). As we found no clear relationship between haplotype and AKT1 transcription in the SBS, further studies are required to elucidate any differential effect in schizophrenic patients (associated with AKT1 or not) versus controls.…”
Section: Discussioncontrasting
confidence: 38%
“…Previously reported SNP309 G allele frequencies in Northern European Caucasians were Ϸ33%, but in African Americans they have been noted to be significantly lower, Ϸ11% (14,24,25). A salient feature of the African Americans and Caucasians figures is that, in both populations, the G allele of SNP309 is highly correlated with all of the other SNPs across the entire region of MDM2 covered by the Celera Diagnostic SNP set, resulting in only one G haplotype in both populations.…”
Section: Resultsmentioning
confidence: 97%
“…For that reason, the haplotype structure of 14 different SNPs in the MDM-2 gene was determined by employing three different racial and ethnic populations: one African American population, one Caucasian not selected for ethnicity, and one Caucasian of the Ashkenazi Jewish ethnic group. These populations were chosen for further haplotype analysis, as it had been previously observed that African Americans have a low G allele frequency, non-Jewish Caucasians an intermediate G allele frequency, and Ashkenazi Jewish groups a high G allele frequency (14,24).The results presented in this report indicate that there are only a few common (Ն1%) G allele haplotypes in all three populations studied, one in the African American and Caucasian data sets and two in the Ashkenazi Jewish data set. The SNPs in the G allele haplotype are thus highly correlated.…”
mentioning
confidence: 99%
“…It is interesting to note that of the SNPs showing significant interaction with OCs defined as OC greater than three and OC greater than four, the minor allele of rs1130233 in AKT1 has been shown to render cells more sensitive to radiation-induced apoptosis, suggesting a functional role for that SNP in AKT1-mediated signaling. 29 Differential maternal recall between cases and controls is not of concern because we used a family-based study design; however, non-directional maternal recall could result in misclassification by serious OC status, which would bias estimates toward the null. The ability of mothers to correctly report obstetric complications decades after birth has been shown to be accurate, 30,31 especially for severe complications or major medical events, although other studies have shown that maternal recall is not always reliable.…”
Section: Discussionmentioning
confidence: 99%